2001
DOI: 10.1038/sj.jhh.1001267
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of a fixed-dose combination of telmisartan plus hydrochlorothiazide in patients uncontrolled with telmisartan monotherapy

Abstract: The antihypertensive effects of a telmisartan 80 mg/hydrochlorothiazide (HCTZ) 12.5 mg fixed-dose combination and telmisartan 80 mg monotherapy were compared in patients with a history of mild-to-moderate essential hypertension and inadequate BP control (DBP у90 mm Hg) following 8 weeks of telmisartan monotherapy. At the end of this period, 491 patients (62.9% men; mean age 55.3 years) whose DBP was у90 mm Hg were double-blind randomised to once-daily telmisartan 80 mg/HCTZ 12.5 mg (n ‫؍‬ 246) or telmisartan 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 25 publications
3
39
0
6
Order By: Relevance
“…In several short-term studies, a fixed combination of telmisartan 40 or 80 mg/day in combination with hydrochlorothiazide 12.5 mg was more effective than the single drugs, with the combination of telmisartan 80 mg/hydrochlorothiazide 12.5 mg being the most effective. [50][51][52][53] An ARB-diuretic combination makes a lot of physiologic sense because each drug has a different mechanism of action, each being complementary to the other. Diuretics increase salt and water excretion and cause plasma volume contraction and decrease in blood pressure, resulting in stimulation of renin release and increased production of AII and aldosterone, which cause vasoconstriction, increase in systemic vascular resistance and salt and water retention, leading to increase in blood pressure, thus counter-balancing the hypotensive effect of diuretics.…”
Section: Angiotensin Receptor Blockers Vs Angiotensin-converting Enzymentioning
confidence: 99%
“…In several short-term studies, a fixed combination of telmisartan 40 or 80 mg/day in combination with hydrochlorothiazide 12.5 mg was more effective than the single drugs, with the combination of telmisartan 80 mg/hydrochlorothiazide 12.5 mg being the most effective. [50][51][52][53] An ARB-diuretic combination makes a lot of physiologic sense because each drug has a different mechanism of action, each being complementary to the other. Diuretics increase salt and water excretion and cause plasma volume contraction and decrease in blood pressure, resulting in stimulation of renin release and increased production of AII and aldosterone, which cause vasoconstriction, increase in systemic vascular resistance and salt and water retention, leading to increase in blood pressure, thus counter-balancing the hypotensive effect of diuretics.…”
Section: Angiotensin Receptor Blockers Vs Angiotensin-converting Enzymentioning
confidence: 99%
“…Obviously, in clinical practice, the most efficient strategy in the presence of a poor response to monotherapy should be not to increase the dose, but to add a diuretic or to shift to another drug, acting through a different mechanism. Accordingly, Lacourcière et al 21 showed that a 'telmisartan 80 mg/HCTZ 12.5 mg fixed dose combination confers significant additional BP reductions compared with continuation of telmisartan monotherapy in nonresponders' (41.5% of patients with normalised BP in the combination treatment group vs 26.1% in telmisartan group; Po0.05), Furthermore, in a recent crossover study by Dickerson et al, 22 a significant correlation was found between the BP responses to angiotensinconverting enzyme inhibitors and betablockers, as well as between those to calcium channel blockers and diuretics, but not between the other four pairing of treatments. Then it could be speculated that patients who fail to respond to renin-angiotensin system blockade should be subsequently given a calcium channel blocker or a diuretic (and conversely).…”
Section: Antihypertensive Effect Of Telmisartan and Of Perindoprilmentioning
confidence: 98%
“…16 Similarly, hydrochlorothiazide greatly enhances the BP depressor effects of telmisartan. 17,18 Moreover, in mild-to-moderate hypertensive patients who did not respond to telmisartan monotherapy, the addition of low-dose hydrochlorothiazide effectively decreased BP in the first 4 weeks of use. 18 More importantly, the antiproteinuric effects of ACE inhibitors are blunted with salt excess, but the addition of hydrochlorothiazide suppresses the salt-induced increase in urinary protein.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Moreover, in mild-to-moderate hypertensive patients who did not respond to telmisartan monotherapy, the addition of low-dose hydrochlorothiazide effectively decreased BP in the first 4 weeks of use. 18 More importantly, the antiproteinuric effects of ACE inhibitors are blunted with salt excess, but the addition of hydrochlorothiazide suppresses the salt-induced increase in urinary protein. 19 Moreover, in the GUARD (Gauging Albuminuria Reduction with Lotrel in Diabetic Patients With Hypertension) trial, 20 benazepril plus hydrochlorothiazide showed superior antialbuminuric effects relative to benazepril plus amlodipine.…”
Section: Discussionmentioning
confidence: 99%